PEDAGOGICAL COMPETENCE OF ENGLISH TEACHER IN OVERCOMING LEARNING DIFFICULTIES OF STUDENTS IN DISTANCE LEARNING DURING COVID-19 PANDEMIC - Nonik Yukafi Mazidah (Language-Edu, 2021)
The learning process be managed professionally by professional educators as well, in order to achieve the goals that are based on an education. In this case, teacher’s pedagogical competence is needed, especially in this Covid-9 era; which obliges the learning process done in distance learning. This research discusses the pedagogical competence of English teachers in overcoming students' learning difficulties. The problems of this research are: first, what is the form of students' learning difficulties perceived by teacher’s perception; and the second, how the efforts of the English teacher pedagogic competence in overcoming the learning difficulties of students. This study employed qualitative design that attempt to explain a phenomenon. Interview was used as the primary tool to collect the data. Furthermore, these interviews provided further insight about the way teacher uses pedagogical competence to overcome students’ learning difficulties in distance learning during covid-19 pandemic. The results of this study show that the pedagogic competence of English teachers can overcome students' learning difficulties. With this competency, the teacher uses herself as a leader in the classroom to manage effective and efficient learning. So that it is an effort to overcome the learning difficulties of students.